2010
DOI: 10.1099/vir.0.018119-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient HLA-DRB1* and -DQB1* allele and haplotype association with hepatitis C virus persistence and clearance

Abstract: Hepatitis C virus (HCV) infection is prevalent throughout the world and interferon (IFN)-based treatments are currently the only therapeutic option. However, depending upon variations in their human leukocyte antigen (HLA), some patients do not respond well to IFN therapy. The current study evaluated the HLA allele and haplotype distribution of 204 HCV-seropositive individuals from Islamabad, Pakistan, who were receiving standard IFN therapy. In this cohort, 150 patients (74 %) showed a sustained virological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
5
22
1
Order By: Relevance
“…These findings were also supported by a cohort study on Pakistani HCV patients treated with IFN therapy which reported that HLA-DRB1*07 individually or in combination with HLA-DQB1*02 was associated with viral persistence, however unlike our results, HLA-DRB1*11 was found to be associated with viral clearance (Ali et al, 2010). In addition, in the Polish population, HLA DRB1*07 and DRB1*13 were more frequent in non-responders and responders to treatment respectively, but without statistical significance (Piekarska et al, 2002).…”
Section: ) -------------------------------------------------------contrasting
confidence: 40%
“…These findings were also supported by a cohort study on Pakistani HCV patients treated with IFN therapy which reported that HLA-DRB1*07 individually or in combination with HLA-DQB1*02 was associated with viral persistence, however unlike our results, HLA-DRB1*11 was found to be associated with viral clearance (Ali et al, 2010). In addition, in the Polish population, HLA DRB1*07 and DRB1*13 were more frequent in non-responders and responders to treatment respectively, but without statistical significance (Piekarska et al, 2002).…”
Section: ) -------------------------------------------------------contrasting
confidence: 40%
“…In summary, it is obvious that none of the host factors studied to date can be used as the sole predictive factor for response to therapy in actual clinical settings. As other polymorphisms were found in the genes of HCV-infected patients, they were shown to be associated with viral persistence or clearance; the HLA-DRB1*07 allele was found to be significantly associated with virus persistence, and HLA-DQB1*0301 was found to be associated with virus clearance [33]. Also, IL12B 3'-UTR 1188-Callele carriers appeared to be capable of responding more efficiently to antiviral combination therapy as a consequence of a reduced relapse rate [34].…”
Section: Discussionmentioning
confidence: 88%
“…were less likely to achieve SVR than carriers of DQB1*0301 (OR 0.32 [41]). The picture is completed by several reproduction failures [42][43][44].…”
Section: Major Histocompatibility Complexmentioning
confidence: 93%